1990
DOI: 10.1007/bf00001186
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of retention of pelagic tomcod, Microgadus tomcod, larvae and juveniles in the well-mixed part of the St. Lawrence Estuary

Abstract: SynopsisWe tested the hypothesis that the mechanism of retention of tomcod, Microgadus tomcod, larvae and juveniles in the well-mixed part of the St. Lawrence Estuary is similar to that of sympatric smelt, Osmerus mordax, larvae who actively migrate to the surface during flood tides and to the bottom during ebb tides so as to minimize net downstream displacement. The vertical distribution of tomcod larvae and juveniles was documented during two 98-h sampling series at 2 anchor stations in June and July, 1986. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
1
9
1
1
Order By: Relevance
“…This observation complements those of Dodson (1989, 1990) who noted that whereas larger pre-metamorphic YOY tomcod were located upstream of smaller tomcod in June, larger postmetamorphic YOY tomcod were located downstream of smaller tomcod in July. These authors suggested that the downstream movement of larger YOY tomcod was related to the dynamics of the retention mechanism with large YOY tomcod more apt to be advected downstream (Laprise and Dodson 1990). Whatever the cause, the present observations suggest that although this situation persists until September, it does not persist through to the following summer.…”
Section: Discussioncontrasting
confidence: 67%
“…This observation complements those of Dodson (1989, 1990) who noted that whereas larger pre-metamorphic YOY tomcod were located upstream of smaller tomcod in June, larger postmetamorphic YOY tomcod were located downstream of smaller tomcod in July. These authors suggested that the downstream movement of larger YOY tomcod was related to the dynamics of the retention mechanism with large YOY tomcod more apt to be advected downstream (Laprise and Dodson 1990). Whatever the cause, the present observations suggest that although this situation persists until September, it does not persist through to the following summer.…”
Section: Discussioncontrasting
confidence: 67%
“…We chose these species because they exhibit different patterns of vertical distribution. Tomcod do not migrate vertically but remain in the deeper layers of the water column (Laprise & Dodson 1990). Smelt larvae undertake tidal vertical migrations, moving to surface waters during floods and closer to the bottom during ebbs (Laprise & Dodson 1989a).…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of several estuarine Neomysis species in ETMs and low-salinity waters (< 5 psu) is associated with the interaction between vertical distribution and estuarine circulation (N. americana: Hulburt 1957, Siegfried et al 1979, Orsi 1986). Finally, the larvae of rainbow smelt are retained in the St. Lawrence ETM by tidal stream transport (Laprise & Dodson 1989), whereas tomcod in the same estuary are retained by remaining in the deep, upstream, residual circulation (Laprise & Dodson 1990). The observed discontinuity in the relative proportions of autotrophs and heterotrophs along the leading edge of the transition zone is due to a variety of mechanisms.…”
Section: Periodicity and Spatial Organizationmentioning
confidence: 99%